Immersion cooling of silicon photomultipliers (SiPM) for nuclear medicine imaging applications. (February 2016) - Raylman, R.R.; Stolin, A.V.
Abstract: Silicon photomultipliers (SiPM) are compact, high amplification light detection devices that have recently been incorporated into magnetic field-compatible positron emission tomography (PET) scanners. To take full advantage of these devices, it is preferable to cool them below room temperature. Most current methods are limited to the cooling of individual detector modules, increasing complexity and cost of scanners made-up of a large number of modules. In this work we investigated a new method of cooling, immersion of the detector modules in non-electrically conductive, cooled liquid. A small-scale prototype system was constructed to cool a relatively large area SiPM-based, scintillator detector module by immersing it in a circulating bath of mineral oil. Testing demonstrated that the system rapidly decreased and stabilized the temperature of the device. Operation of the detector illustrated the expected benefits of cooling, with no apparent degradation of performance attributable to immersion in fluid. Highlights: Immersion cooling is new, simple and inexpensive method to cool solid state based nuclear medicine scanner. Method successfully tested on a scaled version of an SiPM-based PET detector module. Can be scaled up to cool a complete PET scanner.